ECONOMIC EVALUATION OF EGG PRODUCTION: A CASE STUDY IN BOSNIA AND HERZEGOVINA - Falan, Vedad; Mujčinović, Alen; Makaš, Merima; Rustempašić, Alma; Krilić, Alejna (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Poultry production in Bosnia and Herzegovina is one of the strongest and one of the most advanced branches of agriculture from a technological point of view. Evidence suggests that egg production achieves positive financial results as well as a positive trade balance. It is also evident that strong fluctuations sometimes occur, as a result of ever-present market changes but also natural conditions. During the observed period, 2013-2019 egg production in Bosnia and Herzegovina increases by 2.99%, and the average production is 0.7 billion eggs per year. It remains to see whether this promising sector can stimulate agricultural development. Therefore, this study aims to evaluate the economic viability of egg production, as well as to determine major supply and demand trends in egg production/poultry production in Bosnia and Herzegovina. Primary data for this study were collected through semi-structured interviews with representatives of a poultry company in Bosnia and Herzegovina, while secondary data were collected through official statistical agencies, reports, etc. Major production-economic indicators were used for four years (2016-2019). Results showed positive financial results during all observed years, while best performances were evident during the 2018 year and lowest performances were evident during 2017 (66.22% lower compared to 2018). The financial result is mainly influenced by changes in output prices, while companies tend to produce their animal feed which significantly reduces production costs. Also, by-products, poultry fertilizer is highly appreciated by agricultural producers and company make a significant amount of money from it. It remains to see whether egg production can continue to achieve positive results, and is it going to be recognized by policymakers as well as agricultural producers as a more important agricultural branch in Bosnia and Herzegovina.